Cardiovascular risk with long-term use of proton pump inhibitors: myth or reality. A review - Dmitry I. Trukhan; Sergej N. Filimonov (ZAO "Consilium Medicum", 2024)
Proton pump inhibitors (PPIs) are the most effective drugs for treating acid-related diseases. In recent decades, the use of PPIs has increased exponentially. From gastroenterological practice, PPIs are being actively introduced into other specialties, in particular in cardiology and rheumatology, where they are used to protect the mucous membrane of the gastrointestinal tract and prevent gastrointestinal bleeding during long-term antithrombotic therapy and long-term use of non-steroidal anti-inflammatory drugs. For a long time, PPIs were considered completely safe drugs for both short-term and long-term use. However, modern clinical guidelines note that when prescribing PPIs in large doses for a long period, the possibility of side effects should be taken into account. In recent years, a number of foreign reviews have been published that examine the relationship between PPIs and a number of diseases/conditions, including the question of a possible association of PPI use with an increased risk of cardiovascular complications, but note the inconsistency of these data. We searched the PubMed and Scopus information databases for publications on the safety of PPI use, including sources up to 12/01/2023. In this review, we examined the possible cardiovascular risk of long-term use of PPIs. Analysis of publications, despite a number of contradictions, allows us to conclude that the cardiovascular risk with long-term use of PPIs is real and must be taken into account when prescribing PPIs for a long period and to comorbid/multimorbid patients.